Korpusni pristop k izdelavi terminoloških slovarjev - Logar Berginc, Nataša (Jezik in slovstvo, 2008)
The article describes the procedures and treatment of entries for the purposesof a PR terminological dictionary. In the introduction, corroboration is provided of the corpus-based approach to the compilation of terminological dictionaries. A corpus offers numerous technologically and methodologically advanced possibilities for an insight into the set of terms in a particular field. The selection of entries is based on automatically generated lists of field term candidates, i.e., words and collocations that, through statistical analyses and due to their morphosyntactic features, stand out as relevant to aparticular field. Manual examination of lists of terms acquired in this way indicates their usefulness but at the same time reveals some problems related to distinguishing between proper terms and non-terms, or between terms and terminological collocations.
Keywords: Slovene; slovenščina; Terminology (Science); Dictionaries; leksikografija; lexicography; terminologija; terminology; terminološki slovarji; slovarji